The Effect of Financial Performance on BPRs Profitability with Financing to Deposit Ratio as Mediation Variables - Samosir, Hendrik ES; Rawati, Mesis; Amin, Al; Nugroho, Agung; Widjanarko, Widjanarko; Sanadi, Edwin Aldrin W. (Universitas Pendidikan Ganesha, 2025)
The company's financial performance reflects its work plan achievements and can indicate its overall health. This study estimates operating costs, operating income, and profitability with the FDR financing to deposit ratio as a mediating variable that indirectly or directly affects profitability proxied by return on assets ROA in BPRS for the 2015-2023 period. This research is a confirmatory study with a quantitative approach. The data in this study are secondary data obtained from BPRS in the form of annual reports, which are taken quarterly and collected through the official website. Based on the study's results, the path coefficient is partially positive, with a value of 0.72 and a p-value of 0.01 > 0.05. BOPO has a positive and significant effect on ROA, with an influence of 67%. BOPO has a positive and considerable influence on FDR, with an impact of 89%. FDR has a positive and significant effect on Return on Assets ROA with an impact of 35%. Simultaneously, BOPO and FDR affect ROA with an R-squared of 0.669, indicating that the contribution of the influence of BOPO (X) variables and FDR Financing to Deposit Ratio (Z) on Profitability (Return on Assets) is 66.9% and other variables outside the research model and errors influence the remaining 33.1%. The Financing to Deposit Ratio of 0.117 with a P-value of 0.232 greater than 0.05 shows that the Financing to Deposit Ratio cannot mediate the relationship between BOPO and Return on Asset ROA. Implications for Future Research. This study highlights the mediating role of the Financing to Deposit Ratio (FDR) in linking financial performance with BPR profitability. Future research could extend this framework by incorporating additional mediating or moderating variables, such as credit risk, liquidity risk, or governance practices, to capture a more holistic view of profitability drivers. For practitioners, the findings underscore that profitability in BPR is not solely determined by financial performance indicators such as ROA or BOPO, but is also significantly influenced by the efficiency of channeling deposits into financing activities, as captured by FDR.